Stimulus-specific influence of gender on mental-rotation-related brain activity. - Bersier, Nadia M.; Rumiati, Raffaella I.; Ionta, Silvio (Cognitive, Affective & Behavioral Neuroscience, 2025)
Mental rotation (MR) is a cognitive process during which individuals mentally simulate the rotation in space of an object's image (stimulus). The traditional assertion that men outperform women in MR tasks may be influenced by methodological biases, such as treating gender as a secondary or post hoc variable, and relying solely on binary comparisons between two classes of MR stimuli. Furthermore, a comprehensive understanding of how nuanced the effects of the interaction between gender and stimulus type are on MR-related brain activity remains lacking. To fill these gaps, we recorded functional magnetic resonance imaging (fMRI) data while 57 participants (29 women, aged 18–35 years) performed MR of abstract objects, human bodies, and real objects. Whole-brain fMRI data analyses indicated that, with respect to women, men had larger activations in inferior frontal regions during MR of abstract objects, and in superior and medial frontal regions during MR of human bodies. Compared with men, in women we found larger activity in the superior parietal lobe during MR of human bodies with respect to abstract objects, and in the inferior occipital cortex in the MR of real objects versus human bodies. Finally, while in men we found a positive correlation between MR accuracy and brain activity in the precuneus, in women the correlation between MR accuracy and activity in motor and premotor areas was negative. These results indicate that brain activity during MR is modulated by the type of stimulus, differently for women and men.